Micropropagation of Dendrobium Hybrids - Sivamani S (Department of Plant Breeding and Genetics, College of Agriculture, 2004)
Standardisation of protocol for the rapid in vitro propagation of Dendrobium hybrids was attempted. The studies were carried out in the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 2002-2004. Different explants such as immature leaf segment, stem nodal segment and inflorescence axis were used. The effect of different basal media such as MS (full, half and quarter strength), VW (full strength) and KC (full strength) on these explants was studied. The effect of different levels of plant growth substances such as IAA, NAA, Kinetin and BA and different levels of CW on PLB development and plantlet growth was studied. Plant growth substance IBA along with AC was tried for in vitro rooting of microshoots. Among the various explants tried, stem nodal segment responded well showing early PLB differentiation. Since leaf segment and inflorescence axis did not respond even after 45 days of inoculation, they were abandoned and stem nodal segment explant alone was carried forward for further trials. Out of the different basal media tried with stem nodal segment explant, VW medium exhibited early culture establishment and rapid PLB development. Different levels of the hormone combination, BA and NAA tried showed that BA 2.0 mg l-1 + NAA 2.0 mg l-1 responded with the earliest plantlet development, but number of shoots produced was more in BA 8.0 mg l-1 + NAA 8.0 mg l-1. Combination of BA and IAA at different levels showed that BA 2.0 mg l-1 + IAA 4.0 mg l-1 produced plantlets in a minimum number of days. Number of shoots was maximum in BA and IAA each at 8.0 mg l-1. In the combination of KIN and NAA tried at different levels earlier plantlet development was observed in 2.0 mg l-1 each of the auxin and the cytokinin and the number of shoot produced was highest in 8.0 mg l-1 each of KIN and NAA. Among the different levels of KIN and IAA combination tried, 4.0 mg l-1 each of KIN and IAA was found to be the best for rapid plantlet development. Number of shoots produced was highest in the combination KIN 6.0 mg l-1 and IAA 2.0 mg l-1. Out of the three different levels of CW tried, CW 200 ml l-1 was observed to be the best in terms of early plantlet development and the production of more number of shoots. In vitro rooting of microshoots was the best in half strength MS medium supplemented with IBA 2.0 mg l-1. Addition of AC did not produce any significant effect on root development.